Two new species of Antrodia (Polyporales, Basidiomycota) in western China - Zhou, Hong-Min; Liu, Shun; Deng, Xiao-Juan; Liu, Hong-Gao; Xing, Rui; Dai, Yu-Cheng; Wu, Ying-Da (Frontiers in Microbiology, 2023)
Two new species of Antrodia, A. aridula and A. variispora, are described from western China. Phylogeny based on a 6-gene dataset (ITS + nLSU + nSSU + mtSSU + TEF1 + RPB2) demonstrates that samples of the two species form two independent lineages within the clade of Antrodia s.s., and are different in morphology from existed species of Antrodia. Antrodia aridula is characterized by its annual and resupinate basidiocarps with angular to irregular pores of 2–3 per mm, oblong ellipsoid to cylindric basidiospores measuring 9–12 × 4.2–5.3 μm, and growing on gymnosperm wood in a dry environment. Antrodia variispora is characterized by its annual and resupinate basidiocarps with sinuous or dentate pores of 1–1.5 per mm, oblong ellipsoid, fusiform, pyriform or cylindric basidiospores measuring 11.5–16 × 4.5–5.5 μm, and growing on wood of Picea. The differences between the new species and morphological similar species are discussed.